Yolda giden taşıta etkiyen kuvvetlerin devrilme esnasında incelenmesi - Nurol, O. Fatih (Fen Bilimleri Enstitüsü, 1996)
Motorlu araçlarda aktif emniyet tedbirleri çerçevesinde aracm stabilitesi ve yörünge takibi önemli bir yer tutar. Bunlara ilişkili olarak viraj esnasında etkiyen yanal kuvvetlerin, taşıt ekseninin açısal hızına ve hız vektörünün dönme hızına göre değişimi yana yatma dikkate alınarak yalpa ekseni konumu, yörünge takibi ve stabilite arasında matematiksel modeller oluşturulmuş ve bilgisayar kullanarak hesaplamalar yapılmıştır.

It is taken an important situation in order to provide the stability of vehicle and the issuance of rotoue. In addition to the lateral forces on the cornering In addition to the activated safety preventions in the engined vehicles, in addition to the angular velocity change of vehicle and the velocity vector change to the rotational speed. It is taken place the mathematical models. The heading axis between the rotoue issuance and the stability and it is calculated with this computer. It is used linear and nonlinear kinematic constrains in this model. A control law for integrating 4WS and 4WS systems is presented. It is based on a non-linear vehicle model in which the lateral force acting on the tyres changes according to the sleep angle, slip ratio and the load. These maneuvers include cornering with breaking or acceleration as well as vehicle skidding, spinning and rollingover. The generalized velocities used in this model are lateral velocity, V and yaw rate v|/ in this model. It is assumed that the sprung mass center and total vehicle mass center are in the same transverse section of the vehicle. In this study, it is taken a vehicle model as example A vehicle model (h * 0). When the vehicle passes on the contact velocity. The simulation uses a nonlinear eight degree of freedom model which utilizes simple linear subsystems to model the tyres. The vehicle model consists of two masses; a spring mass represent the vehicle chassis and a single unsprung mass which represents the combined front and rear systems. The rollover model simulates the motion of a vehicle which skids laterally onto a pavement and comes into with a road side curb with some small heading angle. The model simulates the skidding motion of the vehicle after impact vehicle rollover is assumed to take place when the roll angle of the unsprung mass exceeds approximately 85°. The simulation uses a nonlinear model which utilizes simple linear subsystems to model and the impact force on the vehicle tyres. The vehicle model consists of two masses; a sprung masses have seperate degree of freedom for roll, lateral translation X and vertical translation, vehicle yaw and pitch being analyzed using a single lumped mass. Design of vehicle linear simulation model. The tyre normal reactions (FzJ, F^, F^, Fz4) are based on a linear tyre deformation model and are proportional to tyre deflections caused by vehicle heave, pitch and roll. The tyre deflections are determined by finding the difference between the undeflected tyre and the distance between the axle and the road surface under each wheel. The tyre lateral sliding forces (Si, S2, S3, S4) are functions of the tyre normal forces, the tyre - surface factional properties and the sliding velocity. The equations of motion for a, e, \\/' and \\i lateral position ( for each mass) were obtained mass and the Newton's second law of motion to the sprung mass and the unsprung mass include gravity and the two forces of the suspension springs and dampers. The sprung mass roll moment equation is; (mhl2 +Ix)i|/ = h'mV(a-+\|/-)+mgh'i|/ -[Ci|/0+C\j/A)i|/-(k\|/0+k\|/A)\|/- (1) The equations of sprung mass lateral and vertical motions are, S,+S2+S3+S4-kNV2a=m[v(a + \(;)-h'v|/] (2).
An analytical model for the rollover linear and nonlinear
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Motorlu taşıtlar; Vektörler; Yanal yükler; Motor vehicles; Vectors; Lateral loads